Enhancing seed yam supply systems in West Africa - Akoroda, M.O.; Cladius-Cole, B.; Kikuno, H.; Okonkwo, C.C.; Aighewi, B.A.; Acha, A.I.; Asiedu, Robert (International Institute of Tropical Agriculture, 2010)
Seed yams are an essential input into the Dioscorea yam economy of West Africa. Till date, the agronomic separation of seed yam production from that of ware tuber production for food has not been fully achieved. ‘Milking’ of food tubers to get seed yam continues as a dominant channel of seed yam supply. Adoption studies indicate the lack of total acceptance of the various suggested procedures for obtaining seed yams by farmers. The relationship of biological feasibilities and economically profitable enterprise are yet to be integrated in any conclusive manner. Until this important socio-economic link is vigorously researched and promoted, our efforts at facilitating the growth and enhancement of the Dioscorea yam sector will remain weak. Efforts to obtain seed yams from vines or mini-setts are still rudimentary in commercial terms and the quantum of knowledge available is yet too low as it is an under-researched aspect of this staple crop. The few dozens of the publications on this important aspect are scattered and the realisation of their total value in the hands of yam farmers is still a long way away. This paper examines the spectrum of options for seed yam supply for commercial systems that produce ware food yam in West Africa—where over 90% of the world’s yam output is produced.